Evaluating the quality and the success of online courses - Peres, Paula (2014)
Measuring the quality of a b-learning environment is critical to determine the success of a b-learning course. There are a lot of materials related to the quality process, namely different approaches and perspectives but none of them is specific of the product of a b-learning context. In this paper we identify the indicators that should be analyzed in order to determine the quality of a b-learning course, since its success reflect not only the student’s perception, but also what should be taken into account. B-Learning environments are relatively new and combine educational characteristics with technological elements that support the learning process and the training delivery. Our main objective is to know what a high quality b-learning environment is in students’’ perception and what are the main quality dimensions of these courses, in the perspective of the products and services offered. After a literature review concerning the quality process and in particular the b-learning quality field, a structure that provides the main elements that should be evaluated by students when we are measuring the quality and the success of b-learning product/services was created. The structure obtained was applied to a case study of the Polytechnic Institute of Oporto. Results presented will help institutions to deliver services with more quality and improve their long-term competitiveness.